A Longitudinal Exploration of Self-Reported Hearing Loss, Tinnitus, and Posttraumatic Stress Disorder Treatment Outcomes in Australian Veterans. Issue 8 (October 2021) - Terhaag, Sonia; Phelps, Andrea; Howard, Alexandra; O'Donnell, Meaghan; Cowlishaw, Sean
ABSTRACT: Objective: Tinnitus, hearing loss, and posttraumatic stress disorder (PTSD) are common conditions among veterans. Shared underlying symptoms, such as hypervigilance and heightened sense of threat, may interfere with talk-based psychological treatments. The aim was to investigate the prevalence and risk factors for self-reported tinnitus and hearing loss among Australian treatment-seeking veterans, as well as links with PTSD symptoms and quality of life (QOL) after treatment. Methods: Australian veterans participating in hospital-based PTSD treatment ( n = 523) completed self-report measures of subjective hearing impairment, service-related factors, PTSD symptoms, and QOL at treatment intake and discharge, as well as 3- and 9-month follow-ups. Univariate analyses of covariance modeled symptom change over time. Results: More than half of veterans on PTSD treatment self-reported doctor-diagnosed hearing loss or tinnitus, whereas 43% reported both. However, 75% reported subjective mild to moderate hearing impairment, and only 1% reported severe impairment. Service-related factors, such as longer length of service and exposure to explosions, were risk factors for having any hearing condition. After controlling for intake scores, there were no significant differences on PTSD or QOL outcomes over time between those with and without hearing conditions. Conclusions: Although self-reported tinnitus and hearing loss are prevalent among veterans, those with severe hearing impairments are unlikely to be represented in this context. There is a need for psychological treatments that are accessible to patients with severe hearing impairments, which should be examined routinely among military members accessing psychological treatments.